2022
DOI: 10.1097/xcs.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Associated with Morbidity and Textbook Outcomes of Laparoscopic Liver Resection in Obese Patients: A French Nationwide Study

Abstract: BACKGROUND: Liver surgeons need to know the expected outcomes of laparoscopic liver resection (LLR) in obese patients. OBJECTIVE: The purpose of the present study is to assess morbidity, mortality and textbook outcomes (TO) after LLR in obese patients. METHODS: This is a French multicenter study of patients undergoing LLR between 1996 and 2018. Obesity was defined by a BMI at or above 30 kg/m2. Short-term ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…With improvement in surgical techniques, operative devices, and perioperative care, postoperative mortality following hepatectomy has been reduced to less than 5%, and even below 1% in some experienced centers 3 , 4 . Unfortunately, the incidence of postoperative complications remains high ranging from 20 to 70% 5 8 . In turn, postoperative complications are independently associated with prolonged hospital stay, increased hospital costs, and a higher risk of early death 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…With improvement in surgical techniques, operative devices, and perioperative care, postoperative mortality following hepatectomy has been reduced to less than 5%, and even below 1% in some experienced centers 3 , 4 . Unfortunately, the incidence of postoperative complications remains high ranging from 20 to 70% 5 8 . In turn, postoperative complications are independently associated with prolonged hospital stay, increased hospital costs, and a higher risk of early death 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…They reported 42% TO for normal BMI, versus 25% for low, and 25.3% for high BMI. Genser et al 51 also found that obesity was associated with a lower chance (58.3 vs 63.7%) to achieve TO in 3154 patients who underwent laparoscopic liver resection in France. In this study, which consisted of a pure open right hepatectomy cohort, no association between BMI and TO was observed.…”
Section: Discussionmentioning
confidence: 96%